Prevalence of Anemia and Its Associated Factors Among Pregnant Women Attending Antenatal Clinic At SOS Hospital In Heliwa District, Mogadishu - Dahie, Hassan Abdullahi; Heyle, Abdullahi Ali (Advances in Social Sciences Research Journal, 2017)
Background: Anaemia in pregnancy is a common problem in most developing countries and a major cause of morbidity and mortality. In pregnancy, anaemia has a significant impact on the health of the foetus as well as that of the mother. 20% of maternal deaths in Africa have been attributed to anaemia. Objective: To assess the prevalence of anemia and its associated factors among pregnant women attending antenatal clinic at SOS Hospital, Heliwa District, in Mogadishu, Somalia 2016. Methodology: Facility based cross-sectional study was conducted at SOS Hospital Heliwa District, in Mogadishu, Somalia 2016, from September to December 2016. Data were collected using pretested questionnaires. A total of 403 pregnant women were included in the study. Data were entered and analyzed using STATA version 12. Both Univariate and Bivariate analysis were carried out to see frequencies and significant associations, a P-value less than 0.05 was considered as significant association. Result: In the study the prevalence of anaemia was 84.3 per cent among pregnant women (340 out of 403). Out of 340, 61(15.14 %) had mild anaemia (hb10 to 10.99 gm/dl), 228 (56.5%) had moderate anaemia (hb 7 to 9.9 gm/dl) and 51 (12.7%) had severe anaemia (hb < 7gm/dl). The study has shown that age of the pregnant women and family size were found to be significant. Pregnant women at age of 25–29 were less likely to be anemic compared to those pregnant women at the age of 20-24 (OR 0.75, 95%CI 0.37 – 0.87). Family size of pregnant women was found to be associated with anemia. Pregnant women whose family size ³ 13 were more likely to be anaemic compared to those whose family size was less than £ 12 (OR 8.41, 95%CI 1.33-52.92). Conclusion and Recommendation: In this study the prevalence of anemia is 84.3% among pregnant women. Comparing the national prevalence of anemia in pregnancy (45.5%) it is higher, needs high effort by other researchers. Sensitization of pregnant women by health providers to encourage early ANC visit and to continue supplements of iron and folate throughout pregnancy. Provision of health education on anemia and importance of visits at least four times during pregnancy and establishment of mobile clinics.